2019
DOI: 10.1159/000500404
|View full text |Cite
|
Sign up to set email alerts
|

Prognosis of Primary Osteosarcoma in Elderly Patients: A Comparison between Young and Elderly Patients

Abstract: Objectives: Osteosarcoma is the most common malignant bone tumor in childhood. Although a poorer prognosis has been described in older patients, few reports have focused solely on primary osteosarcoma. We evaluated the clinical features of elderly patients with primary osteosarcoma. Materials and Methods: Ninety-four patients were included in this retrospective study, and we divided them into 2 groups (older patients and younger patients) based on a cut-off age of 40 years. The patients’ information, including… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(30 citation statements)
references
References 19 publications
4
26
0
Order By: Relevance
“…Increased negative influence of older age was also revealed in other studies. In studies evaluating the cut-off age of 40 or 50 years for osteosarcoma, older patients showed worse survival [12,13]. Besides, the tumor in trunk was more commonly found in older patients and was associated with worse survival in the previous studies and our analysis.…”
Section: Discussionsupporting
confidence: 50%
“…Increased negative influence of older age was also revealed in other studies. In studies evaluating the cut-off age of 40 or 50 years for osteosarcoma, older patients showed worse survival [12,13]. Besides, the tumor in trunk was more commonly found in older patients and was associated with worse survival in the previous studies and our analysis.…”
Section: Discussionsupporting
confidence: 50%
“…In previous studies, good responders were observed in 0%-48% of cases > 40 years old who received neoadjuvant chemotherapy 3 . In our study, only 2 of 9 patients (22%) over 46 years old showed a good response to neoadjuvant chemotherapy, and age < 46 years old was a predictor of a good response to chemotherapy as demonstrated in previous studies 4 , 5 (Table 3 ). The chemotherapy regimen, dose, and the number of courses differed among elderly patients, mainly due to the frequency of adverse events and organ dysfunction with aging, and the efficacy of chemotherapy depended on individual patients’ characteristics 4 , 5 .…”
Section: Discussionsupporting
confidence: 85%
“…In our study, only 2 of 9 patients (22%) over 46 years old showed a good response to neoadjuvant chemotherapy, and age < 46 years old was a predictor of a good response to chemotherapy as demonstrated in previous studies 4 , 5 (Table 3 ). The chemotherapy regimen, dose, and the number of courses differed among elderly patients, mainly due to the frequency of adverse events and organ dysfunction with aging, and the efficacy of chemotherapy depended on individual patients’ characteristics 4 , 5 . However, the multivariate analysis in our study revealed that, rather than the type of drug or number of courses, the age and osteoclast number were predictors of the efficacy of neoadjuvant chemotherapy.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Similarly, the SPOP gene, known as a POZ domain gene is a regulator of skeletal development, and may lead to shorter digit bones and lower bone density 8 . SDHD has an association with abnormality of limb bone (HP:0040068 (HPO_PHENOTYPE_GENE)), SAP30BP 9 , and EIF2S2, EIF4G1,and EIF4A2 all belong to a eukaryotic translation initiation factor gene family that are known to have role in apoptosis in osteosarcoma cells. Osteosarcoma is a type of cancer that produces immature and weak bones 10 .…”
Section: Discussionmentioning
confidence: 99%